A high-safety lithium-ion battery negative electrode material and its preparation and application

By using the rare earth-transition metal cluster prepared by using solvothermal method in lithium-ion batteries as the negative electrode material, the problem of difficulty in suppressing temperature rise in the early stage of lithium-ion battery exothermic reaction is solved, and the safety of the battery is improved through magneto-refrigeration technology, achieving excellent electrochemical performance and lithium storage capacity.

CN115117342BActive Publication Date: 2025-04-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110293455.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-04-11
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

The existing lithium-ion batteries are difficult to effectively suppress the temperature rise in the initial stage of exothermic reaction, resulting in the occurrence of safety accidents. The current magnetic refrigeration materials used in lithium-ion batteries have problems such as low lithium-ion conductivity and varying specific capacity.

Method used

By optimizing components and methods, rare earth-transition metal clusters are prepared by solvothermal method to form magnetic refrigeration materials with nanosheet-like structures, and used as the negative electrode material for lithium-ion batteries.

Benefits of technology

The material exhibits good electrochemical properties, including good rate performance and excellent lithium storage capacity, and has considerable magnetic entropy change value, which can quickly cool down through magneto-cooling technology to improve the safety of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115117342B_ABST
    Figure CN115117342B_ABST
Patent Text Reader

Abstract

The present invention discloses a negative electrode material for lithium-ion batteries and its preparation and application. The negative electrode material is composed of rare earth-transition metal clusters; the negative electrode material presents a nanosheet structure, and the nanosheets are intertwined with each other, and the size of the nanosheets is 10-200nm. The rare earth-transition metal cluster of the present invention is first obtained by a solvothermal method, and the synthesis method is simple and energy-saving. Unlike traditional lithium-ion battery electrode materials, the compound has a large magnetocaloric effect, and the obtained electrode material has magnetic refrigeration characteristics. During the charging and discharging process of the battery, a sudden thermal runaway situation is encountered; magnetic refrigeration can be used to achieve the effect of rapidly cooling the battery system, effectively preventing the occurrence of lithium battery safety accidents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a method for preparing a rare earth-transition metal cluster and an application of the cluster as a negative electrode material in a lithium ion battery. Background Art

[0002] The storage and utilization of energy play an important role in the development of society. Fossil energy has long occupied a major position in the energy structure, but at the same time, fossil energy is also facing problems of resource shortage and environmental pollution. Finding clean renewable energy is an effective means to solve the problems of fossil energy shortage and pollution. The development and utilization of renewable energy has also begun to attract much attention, but renewable energy has encountered problems of discontinuity, instability, and difficulty in grid connection during its development and utilization. Energy storage technology is the key technology to solve its discontinuity and instability problems, and it also makes the development of energy storage technology the key to the practicality of renewable energy. Among the many energy storage technologies, lithium-ion batteries are currently the most mature and complete energy storage technology. Because of their advantages such as high energy density, high operating voltage, long cycle life, and small self-discharge, they are widely used in various portable electronic devices and other power batteries.

[0003] With the popularization and application of lithium-ion batteries, the safety issues of lithium batteries have become increasingly prominent. Especially with the development and application of lithium batteries as power batteries in recent years, a series of safety accidents have also occurred in the process of exploring lithium-ion as a power battery.

[0004] In fact, the process of lithium-ion battery fire and even explosion can be divided into three stages. The first stage is heat release caused by battery overcharging, diaphragm rupture, etc. If the heat is not dissipated in time, a series of events will occur, such as SEI film decomposition and diaphragm melting, causing the battery to produce gas and continue to heat up, eventually leading to fire and explosion. It can be found that if the temperature rise can be effectively suppressed in the initial stage of the exothermic reaction, the occurrence of safety accidents can be suppressed in time. It is easy for us to think of using refrigeration to cool down, but the current traditional refrigeration technology is limited by untimely heat conduction, insufficient refrigeration capacity and difficulty in achieving real-time temperature control. Whether it is possible to design an electrode material with "self-contained refrigeration effect" is a technical problem that researchers have always wanted to solve. Magneto-refrigeration technology is a technical means to solve this problem. Entropy is a physical quantity that measures the degree of disorder of matter. For magnetic materials, the degree of disorder of magnetic moments is called magnetic entropy. According to the second law of thermodynamics, for a reversible process, changes in entropy will cause changes in heat. Magnetocaloric effect refers to the thermal effect that occurs when the magnetic field strength changes in magnetic materials. Magnetocaloric technology is a refrigeration technology that uses the magnetocaloric effect. In this Carnot cycle, unlike the traditional gas compression refrigeration that changes the gas pressure, this process changes the magnetic field strength. Rare earth-based materials are currently a hot topic in magnetic refrigeration research, because rare earth elements have a large number of unpaired electrons in the 4f orbital, which is conducive to obtaining compounds with large magnetic moments. On the other hand, the rich electronic configuration gives rare earth ions a diverse coordination environment, which is conducive to the synthesis of a variety of cluster materials.

[0005] Compared with rare earth-based materials, transition metal-based materials often have lower magnetic entropy, but the magnetic moment point of such materials is close to room temperature, which is conducive to the research of room temperature magnetic refrigeration. In order to solve the problem of low magnetic entropy caused by too low magnetic moment of transition metal elements, researchers designed and synthesized a class of rare earth transition metal clusters. On the one hand, such clusters make up for the problem of single coordination environment of transition metals, which is conducive to the synthesis of high-nuclear clusters. On the other hand, they also increase the magnetic entropy of the material and make the magnetic ordering temperature of the material close to room temperature. It is a magnetic refrigeration material with great application prospects. For example, some researchers used acetate as ligand, Cl - and NO 3- A series of tubular rare earth transition metal clusters were synthesized as mixed anion templates, showing excellent magnetic refrigeration performance.

[0006] However, the magnetic refrigeration materials currently reported publicly cannot be used directly as lithium-ion battery electrode materials due to their low lithium ion conductivity and low specific capacity. Summary of the invention

[0007] In order to solve the above technical problems, the present invention optimizes components and methods, prepares a rare earth-transition metal cluster magnetic refrigeration material by a solvothermal method, and uses the magnetic refrigeration material as a lithium ion battery electrode material.

[0008] The technical solutions specifically adopted in the present invention are as follows:

[0009] The invention provides a negative electrode material for a lithium ion battery. The negative electrode material is composed of rare earth-transition metal clusters. The negative electrode material presents a nano sheet structure, and the nano sheets are intertwined. The size of the nano sheets is 10-200nm.

[0010] Based on the above scheme, preferably, the rare earth metal is gadolinium or lanthanum, the transition metal is iron, cobalt or nickel, and the size of the nanosheet is about 100-150 nm.

[0011] Based on the above scheme, preferably, the composition of the negative electrode material is GdxCoy(BDC)z or GdxFey(BDC)z, wherein the value range of x is 1≤x≤20, the value range of y is 1≤y≤10, and the value range of z is 5≤x≤50.

[0012] Another aspect of the present invention provides a method for preparing the above-mentioned negative electrode material for lithium-ion batteries, the method comprising the following steps:

[0013] 1) adding a rare earth metal salt, a transition metal salt and an organic ligand into a solvent to form a mixed solution;

[0014] 2) stirring the mixed solution of step 1) at room temperature until a clear and transparent solution is formed;

[0015] 3) subjecting the clear and transparent solution of step 2) to a solvothermal reaction at 100-200° C. for 12-24 hours;

[0016] 4) Centrifuging, washing, drying and grinding the mixture after the reaction in step 3) to obtain the lithium ion battery negative electrode material after grinding.

[0017] Based on the above scheme, preferably, the rare earth metal salt is one or two or more of gadolinium nitrate, gadolinium chloride, gadolinium perchlorate, dysprosium nitrate, dysprosium chloride, dysprosium perchlorate, lanthanum nitrate, lanthanum chloride, and lanthanum perchlorate; the transition metal salt is one or two or more of cobalt nitrate, cobalt chloride, nickel nitrate, nickel chloride, ferric nitrate, ferric chloride, ferrous nitrate, ferrous chloride, etc.; the solvent is one or two or more of ethanol, DMF, DEF and DMSO; and the organic ligand is one or two or more of terephthalic acid, isophthalic acid, and phthalic acid.

[0018] Based on the above scheme, preferably, in step 1), the solvent is a combination of two solvents selected from ethanol and DMF, ethanol and DEF, and ethanol and DMSO.

[0019] Based on the above scheme, preferably, in step 1), the molar ratio of the rare earth metal salt to the transition metal salt is 2:(0.9-1.1), and the solid content / solvent concentration in the mixed solution is 15-35 mg / ml; in step 3), the reaction temperature is 150-80°C, and the reaction time is 15-18h; in step 4), the reaction mixture is washed with deionized water and ethanol respectively, and after washing, it is dried at 40-100°C for 8-18h, and more preferably, the drying temperature is 70°C and the drying time is 12 hours.

[0020] Based on the above scheme, preferably, in step 1), the solid content / solvent concentration in the mixed solution is 20-30 mg / ml.

[0021] In another aspect, the present invention provides a lithium ion battery negative electrode comprising the above lithium ion battery negative electrode material.

[0022] Based on the above scheme, preferably, the preparation method of the above lithium ion battery negative electrode is as follows: dissolving the active material: conductive agent: binder in a ratio of 7:2:1 in N-methylpyrrolidone solvent to prepare a slurry and then coating it on copper foil.

[0023] The present invention also provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode, a metal lithium sheet as a counter electrode, a Celgad membrane as a diaphragm, a commercial lithium ion battery 305 electrolyte, and a copper foil as a current collector. The negative electrode shell, the negative electrode, the electrolyte, the diaphragm, the electrolyte, the positive electrode, and the current collector positive electrode shell are stacked and pressed in sequence to assemble into a CR2016 button lithium ion battery.

[0024] Beneficial Effects

[0025] (1) The rare earth-transition metal cluster compound of the present invention is prepared by a low-temperature solvothermal method. The synthesized material has a nanosheet structure and a large specific surface area. At the same time, the nanosheets in the structure are intertwined to form a lithium ion diffusion network, which is conducive to the rapid and stable insertion and extraction reaction of lithium ions in the electrode material. The combined effect of these aspects makes the material exhibit good electrochemical properties, including good rate performance and excellent lithium storage capacity, especially the synthesized Gd 10 Co 7 (BDC) 14 The cluster compound, when applied to the negative electrode of lithium-ion batteries, showed a high capacity of 341.6 mAh g at low rate. -1 In addition, the material also exhibits excellent rate performance, and the discharge capacity can still maintain 190mAh g at a high rate of 5C. -1 In summary, this material has potential application prospects in lithium-ion battery technology.

[0026] (2) The rare earth-transition metal clusters synthesized by the present invention have a considerable magnetic entropy change value, especially the synthesized Gd 10 Co 7 (BDC) 14 The magnetic entropy value of the cluster was 25.77 J kg -1 K -1 , which means that the material has excellent magnetic cooling performance, providing a new idea for improving the safety of lithium-ion batteries. During the charging and discharging process, the battery encounters sudden thermal runaway; magnetic refrigeration can be used to quickly cool the battery system, effectively preventing the occurrence of lithium battery safety accidents. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 These are SEM images of the positive electrode materials prepared in Comparative Examples 1-3 and Examples 1-3.

[0028] Figure 2 Nitrogen adsorption curves of positive electrode materials prepared for Comparative Examples 1-3 and Examples 1-3.

[0029] Figure 3 The figure is a rate performance diagram of the positive electrode materials prepared in Comparative Examples 1-3 and Examples 1-3.

[0030] Figure 4 The magnetic refrigeration performance diagram of the positive electrode materials prepared in Comparative Examples 1-3 and Examples 1-3. DETAILED DESCRIPTION

[0031] Example 1

[0032] Weigh 0.6688 g GdAc 3 , 0.2910g Co(NO 3 ) 2 .6H 2 O and 0.6645g terephthalic acid were placed in a 100mL beaker, 35mL DMF and 35mL ethanol were added, and a clear solution was obtained by stirring at room temperature for 60min. The obtained mixture solution was transferred to a hydrothermal reactor, and then a hydrothermal reaction was carried out at 180°C for 24h. After the hydrothermal reaction was completed and the hydrothermal reactor was cooled to room temperature, the obtained mixture was centrifuged and the supernatant was removed. The mixture was washed with deionized water and ethanol three times and centrifuged. The obtained lavender powder was placed in a vacuum drying oven at 60°C and dried for 12h to obtain the final product Gd 10 Co 7 (BDC) 14 .

[0033] Example 2

[0034] Weigh 0.6865 g Gd(NO 3 ) 3 , 0.1739 g Fe(Ac) 2 and 0.6645g terephthalic acid in a 100mL beaker, add 35mL DMF and 35mL ethanol, stir at room temperature for 60min to obtain a clear solution, transfer the resulting mixture solution to a hydrothermal reactor, and then carry out a hydrothermal reaction at 180°C for 24h. After the hydrothermal reaction is completed and the hydrothermal reactor is cooled to room temperature, the resulting mixture is centrifuged and the supernatant is removed, washed with deionized water and ethanol three times and centrifuged, and the obtained light yellow powder is placed in a vacuum drying oven at 60°C and dried for 12h to obtain the final product Gd 12 Fe 7 (BDC) 15 .

[0035] Example 3

[0036] Weigh 0.8233g Dy(Ac) 3 .4H 2 O, 0.1739 g Fe(Ac) 2 and 0.6645g terephthalic acid in a 100mL beaker, add 35mL DMF and 35mL ethanol, stir at room temperature for 60min to obtain a clear solution, transfer the resulting mixture solution to a hydrothermal reactor, and then carry out a hydrothermal reaction at 180°C for 24h. After the hydrothermal reaction is completed and the hydrothermal reactor is cooled to room temperature, the resulting mixture is centrifuged and the supernatant is removed, washed with deionized water and ethanol three times and centrifuged, and the obtained light yellow powder is placed in a vacuum drying oven at 60°C and dried for 12h to obtain the final product Dy 10 Fe 6 (BDC) 15 .

[0037] Comparative Example 1

[0038] Weigh 0.6956g Fe(Ac) 2 and 0.6645g terephthalic acid in a 100mL beaker, add 35mL DMF and 35mL ethanol, stir at room temperature for 60min to obtain a clear solution, transfer the resulting mixture solution to a hydrothermal reactor, and then carry out a hydrothermal reaction at 180°C for 24h. After the hydrothermal reaction is completed and the hydrothermal reactor is cooled to room temperature, the resulting mixture is centrifuged and the supernatant is removed, washed with deionized water and ethanol three times and centrifuged, and the resulting yellow powder is placed in a vacuum drying oven at 60°C and dried for 12h to obtain the final product Fe 2 (BDC) 3 .

[0039] Comparative Example 2

[0040] Weigh 0.6688g Gd(Ac) 3 and 0.6645g terephthalic acid in a 100mL beaker, add 35mL DMF and 35mL ethanol, stir at room temperature for 60min to obtain a clear solution, transfer the resulting mixture solution to a hydrothermal reactor, and then carry out a hydrothermal reaction at 180°C for 24h. After the hydrothermal reaction is completed and the hydrothermal reactor is cooled to room temperature, the resulting mixture is centrifuged and the supernatant is removed, washed with deionized water and ethanol three times in succession and centrifuged, and the resulting yellow powder is placed in a vacuum drying oven at 60°C and dried for 12h to obtain the final product Gd 2 (BDC) 3 .

[0041] Comparative Example 3

[0042] 0.272 g of sodium acetate trihydrate (NaAc·3H 2 O, 2.0mmol), 4mL 1.0mol·L -1 Gadolinium perchlorate (Gd(ClO 4 ) 3 , 4mmol), 0.174g ferrous acetate (Fe(Ac) 2 , 1mmol) was placed in 10mL of ethanol and treated with 1mol·L -1 Sodium hydroxide solution was used to adjust the pH value of the above solution to about 5, and then heated under reflux at about 70°C for 2 hours. The solution was filtered to obtain a reddish brown solution, and the filtrate was slowly evaporated at room temperature until reddish brown crystals were grown: Gd 6 Fe 13 C 24 H 136 Cl 13 O 142 .

[0043] The negative electrode materials of lithium ion batteries prepared in the above-mentioned embodiments and comparative examples were dissolved in N-methylpyrrolidone solvent in a ratio of active material: conductive agent: binder = 7:2:1 to prepare slurry, and then coated on copper foil to obtain a negative electrode of a lithium ion battery. A metal lithium sheet was used as a counter electrode, a Celgad film was used as a diaphragm, a commercial lithium ion battery 305 electrolyte was selected, and a copper foil was used as a current collector. The negative electrode shell, the negative electrode, the electrolyte, the diaphragm, the electrolyte, the positive electrode, and the current collector positive electrode shell were stacked and pressed in sequence to assemble into CR2016 button-type lithium ion batteries, and charge and discharge tests were carried out at 0.2C, 0.5C, 1C, 2C and 5C rates, respectively. In addition, the variable temperature and variable field magnetization curve test was carried out on the embodiments and comparative examples to obtain the magnetic entropy change value of the compound.

[0044] The test results are shown in Table 1 and Figure 1-4 shown.

[0045] Table 1. Specific surface area and performance test results of the positive electrode materials prepared in each embodiment and comparative example

[0046]

[0047] from Figure 1 It can be seen that the SEM images of Examples 1-3 all show nanosheet structures. The low-temperature solvent thermal method used can effectively control the uniformity of the material particle size, forming a rare earth-transition metal cluster nanomaterial with a particle size range of less than 200nm. Such a structure can effectively increase the contact area between the material and the electrolyte, thereby increasing the diffusion rate of lithium ions in the material, thereby improving the electrochemical performance of the material. In addition, the nanosheet structure is conducive to increasing the specific surface area of ​​the material, such as Figure 2 As shown, the specific surface area values ​​of the embodiments are better than those of the comparative examples, thus providing more active sites during the electrochemical reaction.

[0048] like Figure 3 As shown, the rate performance of Example 1, Example 2, and Example 3 is significantly better than that of Comparative Example 1. At a rate of 0.2C, Comparative Example 1 exhibited a rate of 180.0 mAh g -1 The lithium storage capacity of Example 1, Example 2 and Example 3 respectively showed 376.7 mAh g -1 and 341.6mAh g -1 , 280.4mAh g -1 The discharge specific capacity of the Gd synthesized in Example 2 is much higher than that of the comparative example 1. 7 Co 10 (BDC) 14 When used as negative electrode material, the lithium storage capacity can reach 190 mAh g at a high rate of 5C. -1 It can be seen that Examples 1-3 all exhibited high reversible lithium storage capacity at low rates, which is beneficial to improving the energy density of lithium-ion batteries and is of great significance in the practical research of negative electrode materials for lithium-ion batteries.

[0049] like Figure 4 As shown in the figure, the magnetic entropy change values ​​of the embodiment and the comparative example are calculated by testing the variable temperature and variable field magnetization intensity curve. It should be noted that the magnitude of the magnetic entropy change value directly indicates the magnetic cooling performance of the material itself. The maximum value of the magnetic entropy change of embodiment 1 and embodiment 2 can reach 25.77 J kg -1 K -1 and 16.35 J kg -1 K -1, while for Example 3 and Comparative Example 1, the magnetic entropy change value is only 6.88 J kg -1 K -1 and 5.49 J kg -1 K -1 The main reason is that the rare earth element Dy selected in Example 3 has a larger anisotropy, resulting in a smaller magnetic cooling property. For Comparative Example 2, since no rare earth metal salt is added to the raw materials, the number of single electrons in the synthesized material is smaller, and therefore the magnetic entropy is also smaller.

[0050] In summary, the rare earth-transition metal cluster material synthesized in the present invention not only has excellent magnetocaloric properties, but also has excellent lithium storage performance as anode material for lithium-ion batteries. The present invention provides a new idea and strategy for solving the current prominent lithium battery safety problem.

Claims

1. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material is composed of rare earth-transition metal clusters; the negative electrode material presents a nanosheet structure, and the nanosheets are intertwined with each other, and the size of the nanosheets is 10-200nm; The composition of the negative electrode material is GdxCoy(BDC)z or GdxFey(BDC)z, wherein x is in the range of 1≤x≤20, y is in the range of 1≤y≤10, and z is in the range of 5≤z≤50.

2. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that: The size of the nanosheets is 100-150 nm.

3. A method for preparing the negative electrode material for a lithium ion battery according to claim 1, characterized in that: The method comprises the following steps: 1) adding rare earth metal salt, transition metal salt and organic ligand into a solvent to form a mixed solution; 2) stirring the mixed solution of step 1) at room temperature until a clear and transparent solution is formed; 3) subjecting the clear and transparent solution of step 2) to a solvothermal reaction at 100-200° C. for 12-24 hours; 4) Centrifuging, washing, drying and grinding the mixture after the reaction in step 3) to obtain the lithium-ion battery negative electrode material after grinding.

4. The method for preparing a negative electrode material for a lithium ion battery according to claim 3, characterized in that: In step 1), The rare earth metal salt is one or two or more of gadolinium nitrate, gadolinium chloride and gadolinium perchlorate; The transition metal salt is one or two or more of cobalt nitrate, cobalt chloride, ferric nitrate, ferric chloride, ferrous nitrate, ferrous chloride, etc.; The solvent is one or more of ethanol, DMF, DEF and DMSO; The organic ligand is terephthalic acid.

5. The method for preparing a negative electrode material for a lithium ion battery according to claim 4, characterized in that: In step 1), the solvent is a combination of two solvents selected from ethanol and DMF, ethanol and DEF, and ethanol and DMSO.

6. The method for preparing a negative electrode material for a lithium ion battery according to claim 3, characterized in that: In step 1), the molar ratio of the rare earth metal salt to the transition metal salt is 2:(0.9-1.1), and the solid content / solvent concentration in the mixed solution is 15-35 mg / ml; In step 3), the reaction temperature is 150-180°C and the reaction time is 15-18h; In step 4), the reaction mixture is washed with deionized water and ethanol respectively, and then dried at 40-100° C. for 8-18 h.

7. The method for preparing a negative electrode material for a lithium ion battery according to claim 6, characterized in that: In step 1), the solid content / solvent concentration in the mixed solution is 20-30 mg / ml.

8. A negative electrode for a lithium ion battery, characterized in that: The invention comprises the lithium-ion battery negative electrode material according to claim 1.

9. Use of the lithium ion battery negative electrode material according to claim 1 in a lithium ion battery.

Citation Information

Patent Citations

  • Co2 (BDC) 2 ted negative electrode material for lithium ion battery

    CN109873157A

  • Ce-doped Fe-MOF ozone catalyst, and preparation and application thereof

    CN111715294A